La violencia de hijos adolescentes contra sus progenitores La violencia de hijos adolescentes contra sus progenitores - Concepción Aroca Montolío (Revista Sobre la Infancia y la Adolescencia)
According to Prosecutor’s Office of the Minor, the accusation interposed by mothers and/or fathers victims by theirs children, along 2007 were 2603, in 2008 amounted 4.211, in 2009 there were 5.209 and in 2010 there were 8.000 accusations. Suede this worrying increase, the principal aim of our article is to check the scientific international and national documentation, from 1957 until the year 2010 that analyses the phenomenon of the adolescent violence against parents, to achieve an approximation to its keys that there allows us the comprehension and analysis of this serious familiar problem. For it we will analyse: (a) the importance of this crime by means of criminological mediators: prevalence and incidence; (b) the age and sex variables’ aggressors to be able to establish a basic profile about theirs and, (c) the violence types that the teenagers wield to damage, prejudice and suffering against their progenitors, with the aim to obtain what they want. The information obtained in this research review and qualitative analysis, change in base to the methodology used and the type of sample under study to obtain conclusions. Even though, we wantto do research into needs to investigate this type of familiar violence, and from there, to do researches with rigorous scientific methodologies, unifying criteria and variables to be investigating, to be able to anticipate in this increasing problem that the parents have.   Según la Fiscalía del Menor en el año 2007, las denuncias interpuestas por madres y/o padres, víctimas de malos tratos por sus hijos e hijas menores de edad, fueron 2.683. En 2008 ascendieron a 4.211, en 2009 se presentaron 5.209 y en el año 2010 se registraron 8.000 denuncias. Ante éste preocupante incremento, el objetivo principal de nuestro artículo es revisar la documentación científica que analiza la violencia filio-parental,  desde 1957 hasta el año 2011, para lograr una aproximación a sus claves que nos permita la comprensión y análisis de este grave problema familiar. Para ello, analizaremos: (a) la gravedad del delito a partir de los medidores criminológicos de la prevalencia e incidencia; (b) las variables de edad y sexo de los hijos para poder establecer un perfil básico del agresor y, (c) los tipos de violencia que éste ejerce para causar daño, perjuicio y sufrimiento a sus progenitores, con el objetivo de obtener lo que desea. Los datos obtenidos en nuestra revisión documental y análisis cualitativo varían según la metodología utilizada y el tipo de muestra bajo estudio impidiendo, en la mayoría de los casos, establecer conclusiones. Con ello, queremos demostrar la necesidad de investigar este tipo de violencia familiar para, y a partir de ahí, diseñar estudios con rigurosas metodologías científicas, unificando criterios y variables a investigar, para poder prevenir el creciente problema al que se enfrentan madres y padres.